Development of novel hyperpolarized magnetic resonance techniques for metabolic imaging of the heart - Schroeder, MA (2009)
The advent of hyperpolarized magnetic resonance (MR) has provided new potential for real-time visualization of in vivo metabolic processes. The aim of the work in this thesis was to use hyperpolarized substrates to study rapid metabolic processes occurring in the healthy and diseased rat heart. Initial work, described in Chapter 2, optimized the hyperpolarization process to reproducibly generate tracers. Chapter 3 describes use of hyperpolarized 1-13C-pyruvate to investigate in vivo flux through the regulatory enzyme pyruvate dehydrogenase (PDH). Cardiac PDH activity was altered in several physiological and pathological states, namely fasting, type 1 diabetes, and high-fat feeding, and in vivo flux through PDH was measured using hyperpolarized MR. These measurements correlated with measurements of in vitro PDH activity obtained using a validated biochemical assay. The work in Chapter 4 investigated the physiological interaction between hyperpolarized tracer and cardiac tissue. The effect of hyperpolarized 1-13C-pyruvate concentration on its in vivo metabolism was analyzed using modified Michaelis-Menten kinetics. It was found that hyperpolarized MR could non-invasively follow mechanisms of metabolic regulation, in addition to reporting enzyme activity. In Chapter 5, hyperpolarized MR was incorporated into the isolated perfused rat heart. 1-13C-pyruvate in normal and ischaemic hearts revealed significant differences in lactate metabolism, and provided the foundation for a novel intracellular pH probe. Infusion of 2-13C-pyruvate in the isolated rat heart enabled the first real-time visualization of Krebs cycle intermediates. In summary, the work in this thesis has highlighted the potential of hyperpolarized MR to reveal novel information on heart disease.